Mediterranean Architecture - Tammy Gaber (International Institute of Islamic Thought, 2004)
Organized by the Faculty of Engineering on February 15-18, 2004 at Misr International University, one of Egypt’s leading private universities, the Department of Architecture and Dean Salah Zaky Said targeted a diverse audience of architects and professionals. The varied responses and interpretations of the conference’s title proved that this provocative subject allowed for multilayered discussions. The dialogue between academics, students, and professionals from different backgrounds identified meanings with respect to the Mediterranean basin’s architecture. The following themes were discussed: the social impact on Mediterranean architecture, technology and crafts, urbanism and development, landscape and environment, trends in current architecture, and heritage conservation. The conference started with the keynote speech delivered by Suha Ozkan (secretary of the Aga Khan Award), who traced the landmark works of contemporary architecture in the Mediterranean basin. The solutions presented addressed issues not only of regional aesthetics, but also of climatic and cultural relevance. The second keynote speaker was Italian academic and architect Attilio Petruccioli (dean, School of Architecture, University of Bari, Italy), who brought up themes of typology and specificity in architecture. A rich discussion followed, with one of the session chairmen, Aga Khan Award recepient Abdel Halim Ibrahim (architect and professional, University of Cairo, Egypt), questioning and provoking the audience with respect to the meaning of the built form and material in this region. The presentation of papers started with the theme of “Social Impact on Mediterranean Architecture.” Papers explored ideas of cultural identity in ...